Цифрова трансформація педагогічної освіти: інструменти, платформи та методики підготовки майбутніх учителів - Кіт, Іванна; Кириленко, Неля (Вінниця : Твори, 2026)
The article provides a comprehensive study of the process of digital transformation of teacher education in the context of the development of the information society. Modern approaches to the formation of future teachers’ digital competence are analyzed, and digital tools, platforms, and innovative teaching methods are characterized. Particular attention is paid to international experience in the digitalization of education, as well as to the challenges and risks that arise in the process of transforming the educational environment. Promising directions for the development of teacher education in the context of digital transformation are identified.
Стаття містить комплексне дослідження процесу цифрової трансформації педагогічної освіти в умовах розвитку інформаційного суспільства. Проаналізовано сучасні підходи до формування цифрової компетентності майбутніх учителів, охарактеризовано цифрові інструменти, платформи та інноваційні методи навчання. Особливу увагу приділено міжнародному досвіду цифровізації освіти, а також викликам і ризикам, що виникають у процесі трансформації освітнього середовища. Визначено перспективні напрями розвитку педагогічної освіти в контексті цифрової трансформації.
Keywords: digital transformation; teacher education; digital competence; цифрова трансформація; педагогічна освіта; цифрова компетентність; інноваційні технології